Trajectories of perceived susceptibility to COVID-19 over a year: The COVID-19 & chronic conditions (C3) cohort study. Issue 24 (17th June 2022) - Opsasnick, Lauren A.; Curtis, Laura M.; Kwasny, Mary J.; O'Conor, Rachel; Wismer, Guisselle A.; Benavente, Julia Yoshino; Lovett, Rebecca M.; Eifler, Morgan R.; Zuleta, Andrea M.; Bailey, Stacy Cooper; Wolf, Michael S.
Abstract : Abstract: The U.S. public health response to coronavirus disease 2019 (COVID-19) has been widely criticized as having downplayed the potential implications COVID-19 could have on one's personal health. Despite the unprecedented threat of COVID-19, many individuals still believed that it was not at all likely that they would become infected. We sought to investigate trends in adults' perceived susceptibility to COVID-19 over the first year of the pandemic, whether distinct trajectories emerged, and if these trajectories differed by participant socio-demographic characteristics. This was a longitudinal cohort study with 5 time points of data collection (March 13, 2020–March 3, 2021). Subjects included 627 adults living with ≥1 chronic conditions, who completed a baseline interview and at least one follow-up interview. In addition to collecting relevant socio-demographic characteristics, participants' perceived susceptibility to COVID-19 across time was assessed and classified into distinct trajectories. Nearly two-thirds (62.2%) of participants perceived themselves to be highly susceptible to COVID-19 from the onset of the pandemic ("early responders") and sustained this over a year, a third (29.0%) eventually perceived themselves to be highly susceptible ("late responders"), and 8.8% maintained a low likelihood of susceptibility throughout the pandemic ("non-responders"). In multivariable analyses, compared to White participants, Latinx participants were significantly more likely to be non-responders and report low likelihood of perceived susceptibility (Risk Ratio [RR]: 3.46; 95% confidence interval: 1.19, 10.1), as were Black participants (RR: 5.49; 95% confidence interval: 2.19, 13.8). A year into the COVID-19 pandemic, 1 out of 11 participants persistently did not think they might be susceptible and potentially infected. Future studies are needed to understand reasons why certain individuals, particularly those of racial/ethnic minorities, did not perceive themselves at risk for infection.